The vertebrate middle and inner ear: A short overview. (17th August 2018) - Pfaff, Cathrin; Schultz, Julia A.; Schellhorn, Rico
Abstract : The evolution of the various hearing adaptations is connected to major structural changes in nearly all groups of vertebrates. Besides hearing, the detection of acceleration and orientation in space are key functions of this mechanosensory system. The symposium "show me your ear – the inner and middle ear in vertebrates" held at the 11th International Congress of Vertebrate Morphology (ICVM) 2016 in Washington, DC (USA) intended to present current research addressing adaptation and evolution of the vertebrate otic region, auditory ossicles, vestibular system, and hearing physiology. The symposium aimed at an audience with interest in hearing research focusing on morphological, functional, and comparative studies. The presented talks and posters lead to the contributions of this virtual issue highlighting recent advances in the vertebrate balance and hearing system. This article serves as an introduction to the virtual issue contributions and intends to give a short overview of research papers focusing on vertebrate labyrinth and middle ear related structures in past and recent years. Abstract : Rat skull with virtually reconstructed middle ear ossicles and bony labyrinth endocast. This virtual issue of the Ear‐symposium of the 11th ICVM 2015 intend to present current research addressing adaptation and evolution of the vertebrate ear region.